The use of the HPV vaccine and its main relationships with cervical cancer (Research, Society and Development, 2020)
The Human Papillomavirus (HPV) comes from the Papillomaviridae family and the genus Papillomavirus. It is known to be a sexually transmitted virus and not enveloped. It causes anorectal lesions such as condyloma acuminata, squamous cell carcinoma and its precursor, intraepithelial neoplasia. Anti-HPV vaccines were launched with the aim of preventing infection by the virus, thereby reducing the development of cervical neoplasms. Thus, the present work aims to describe the importance of vaccination against the HPV virus and its relationship with cervical cancer. It is a descriptive study, of the type integrative literature review, of a qualitative character since it is defined as a type of investigation focused on the qualitative aspect of a given question. For the accomplishment of this study, the databases were consulted : MEDLINE, Scholar Google and SCIELO. The Health Sciences Descriptors (DeCS) were used in an associated way: "Human Papillomavirus", "Cervical Cancer", "Vaccine" and "Prevention". After applying the inclusion criteria, 13 studies remained. Effective and safe HPV vaccines could be important tools for preventing cervical cancer worldwide, particularly in developing countries. The expectation is that in 10 to 20 years there may be a reduction in the incidence rates of the precursor lesions of this cancer and, gradually, a reduction in cancer, which is the second leading cause of death of women from neoplasms worldwide.